Предмет:
МатематикаАвтор:
аноним3б + (5а - 7б) = 3б + 5а - 7б = 5а - 4б;
-3q - (8р - 3q) = -3q - 8p + 3q = -8p;
(2 + 3а) + (7а - 2) = 2 + 3a + 7a - 2 = 10a;
-(11а + б) - (12а - 3б) = -11а - б - 12а + 3б = 2б - 23а;
а + (а - 10) - (12 + а) = а + а - 10 - 12 - а = а - 22;
(6х - 8) - 5х - (4 - 9х) = 6х - 8 - 5х - 4 + 9х = 10х - 12;
5х + (11 - 7х) = 5х + 11 - 7х = 11 - 2х;
-(8с - 4) + 4 = -8с + 4 + 4 = 8 - 8с;
(5 - 3б) + (3б - 11) = 5 - 3б + 3б - 11 = -6;
(5а - 3б) - (2 + 5а - 3б) = 5а - 3б - 2 - 5а + 3б = -2;
(1 - 9у) - (22у - 4) - 5 = 1 - 9у - 22у + 4 - 5 = -31у;
5б - (6б + а) - (а - 6б) = 5б - 6б - а - а + 6б = 5б - 2а.
Автор:
eduardoburnsДобавить свой ответ
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть